Leaf synchrony and insect herbivory among tropical tree habitat specialists - Lamarre, Greg P. A.; Mendoza, Irene [UNESP]; Fine, Paul V. A.; Baraloto, Christopher (Springer, 2014)
Growth defense tradeoff theory predicts that plants in low-resource habitats invest more energy in defense mechanisms against natural enemies than growth, whereas plants in high-resource habitats can afford higher leaf loss rates. A less-studied defense against herbivores involves the synchrony of leaf production, which can be an effective defense strategy if leaf biomass production exceeds the capacity of consumption by insects. The aim of this study was to determine whether leaf synchrony varied across habitats with different available resources and whether insects were able to track young leaf production among tree habitat specialists in a tropical forest of French Guiana. We predicted that high-resource habitats would exhibit more synchrony in leaf production due to the low cost and investment to replace leaf tissue. We also expected closer patterns of leaf synchrony and herbivory within related species, assuming that they shared herbivores. We simultaneously monitored leaf production and herbivory rates of five pairs of tree species, each composed of a specialist of terra firme or white-sand forests within the same lineage. Our prediction was not supported by the strong interaction of habitat and lineage for leaf synchrony within individuals of the same species; although habitat specialists differed in leaf synchrony within four of five lineages, the direction of the effect was variable. All species showed short time lags for the correlation between leaf production and herbivory, suggesting that insects are tightly tracking leaf production, especially for the most synchronous species. Leaf synchrony may provide an important escape defense against herbivores, and its expression appears to be constrained by both evolutionary history and environmental factors.
Keywords: Phenology; Escape; Herbivorous insects; Resource availability; Time lag; French Guiana